FRENCH PRESS IN THE METHODOLOGY OF TEACHING FRENCH AS A FOREIGN LANGUAGE - Khourshida Khodjayeva (Web of Journals Publishing, 2024)
The author considers the role and possibilities of using the French press in the methodology of teaching French. Leaving aside a whole layer of general French language teaching literature, which in one way or another includes excerpts from French newspapers and magazines, the author turns directly to books that focus on the language of the French press. The most famous Russian textbooks on the language of French media are analysed because they are oriented to the Russian-speaking student and include, for example, materials on translation (from Russian into French and vice versa). The analysis allows us to present a general typology of manuals devoted to the French press, depending on their objectives. First of all, the author singles out the manuals aimed at studying the specifics of the French printed word itself, its history and current state. It is argued that the largest share is made up of books where the press is used as a material for acquiring and consolidating practical skills, for actively expanding the vocabulary of French language learners, and manuals on abstracting in French (composing the three main types of retelling, called in the French methodological tradition résumé, compte rendu, synthèse), based on the material of French periodicals and gaining popularity due to the need to pass the international examinations DELF / DALF.
Keywords: French press; French as a foreign language; teaching methods; typology; history of French press; lexical exercises; abstracting in French.